Exploring the association between nutrition knowledge and generalized anxiety disorder among young adults in the Kingdom of Saudi Arabia: implications for Saudi Vision 2030 - Ghabashi, Mai Adil (Frontiers in Nutrition, 2025)
ObjectivesAnxiety is the most prevalent mental health issue in the Kingdom of Saudi Arabia (KSA), particularly among young adults, who face significant challenges in managing it, such as social stigma surrounding mental health, which may also discourage them from seeking help. Within the context of Saudi Vision 2030, addressing challenges and promoting the overall health and psychological wellbeing of the population is a vital public health objective. Consequently, it is suggested that exploring the potential role of nutrition knowledge as a strategy to promote overall health and wellbeing warrants further investigation. To address this gap, the present study aimed to examine the association between nutrition knowledge and distinct factors, including Generalized Anxiety Disorder (GAD), among young adults in the KSA.MethodsThis cross-sectional study included 444 participants. Validated questionnaires assessing nutrition knowledge and specific aspects of mental health were administered in Arabic. Linear and logistic regression analyses were then employed to examine the associations between nutrition knowledge and various aspects of mental health.ResultsIt was found that 51.3% of the participants did not have a satisfactory level of nutrition knowledge, while 35.1% were affected by GAD. Notably, a high level of nutrition knowledge emerged as a protective factor against the risk of developing GAD among young Saudi adults. Specifically, the probability of developing GAD was 40% lower among youth with satisfactory nutrition knowledge, compared to those with unsatisfactory knowledge (OR = 0.6, 95% CI; 0.3 to 0.9; p = 0.02). Furthermore, the completion of nutrition-related courses emerged as a predictive factor for having a satisfactory level of nutrition knowledge. Individuals who had completed nutrition courses were ~4.6 times (95% CI; 2.9–7.4; p < 0.001) more likely to demonstrate a satisfactory level of nutrition knowledge, in comparison to those who had not taken such courses.ConclusionTo the best of my knowledge, this study is the first to investigate the association between nutrition knowledge and GAD in young Saudi adults. The findings suggest that the implementation of targeted nutrition education interventions may serve as a promising strategy to enhance overall health and wellbeing among the young population living in the KSA. Utilizing technology and social media may facilitate the delivery of these interventions, making them more accessible and engaging for young Saudi individuals.